PENGEMBANGAN FORMULASI MASKER EKSTRAK AIR DAUN ALPUKAT (Persea americana Mill) SEBAGAI ANTIBAKTERI Staphylococcus aureus UNTUK PENGOBATAN JERAWAT - Nur Ismiyati; Tri Lestari (Pharmaciana, 2014)
Skin problems are often on the spotlight, one of them is acne. Inflammation of acne can betriggered by the bacteria Propionibacterium acne, Staphylococcus epidermidis and Staphylococcusaureus. One of the herbs that can be used for acne treatment is the leaves of avocado (Perseaamericana). This study aims to determine the potential antibacterial activity of avocado leafwater extract on the growth of Staphylococcus aureus bacteria that causes acne and mask-makingformulation preparation. Antibacterial activity test was carried out by the diffusion method and theobserved inhibition zone that occured in a series of concentrations of avocado leaf water extract (15%, 17.5% , 35% , 50% , 75%). Antibacterial activity test was also conducted on some avocado leafwater extract mask formula (17.5% , 35% , 50% , 75%) was evaluated the physical properties of themask and irritation test was done. The results showed that the avocado leaf water extract mask formulahad antibacterial activity greater than the extract form. The physical condition evaluation and irritationtest showed that the best mask formulation was concentration of 35%.